Pengaruh persepis,Pengetahuan dan Sikap Masyarakat Kelurahan Curug Kulon terhadap Minat Menggunakan Produk Bank Syariah - Dewi Reni; Adam Jodi (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2021)
This study aims to determine "The Influence of Perception, Knowledge, and Attitudes of the Community of Curug Kulon Village, Curug-Tangerang on Interest in Using Islamic Bank Products". The research method used in this study is a quantitative research method and tested by statistical testing using multiple linear regression techniques. The results of the dependent variable in this study are Interest in Using Islamic Bank Products while the independent variable is Public Perception, Knowledge, and Attitudes About Islamic Banks. This study used a questionnaire as many as 88 respondents who were processed using IBM SPSS 23 software. The results of the partial study (T test) showed that the variables of Perception, Knowledge, and Attitude of the community in Kp. Candu RT 01 RW 07 Curug Kulon Village, Curug Subdistrict, has a significant effect on Interest in Using Islamic Bank Products. Simultaneously, it shows that the variables of Perception, Knowledge, and Attitude have a significant effect on Interest in Using Islamic Bank Products. The R-Square value is 0.827 (82.7%). shows that the independent variables, namely Perception, Knowledge, and Attitude are able to explain the dependent variable of Interest by 82.7% while the remaining 18% is explained by other variables not examined in this study.